Understanding Significant Factors of Attitude and Purchase Intention of Online Customers Toward E-Commerce in China - Yang, Jueran (Scholar: Human Sciences, 2024)
Purpose: The primary objective of this study is to examine the factors that shape the attitudes and purchase intentions of Chinese online shoppers in relation to online shopping within China. To achieve this, a conceptual framework was constructed using the Theory of Reasoned Action (TRA) and the Technology Acceptance Model (TAM). The framework encompasses perceived usefulness, perceived ease of use, attitude, trust, perceived risk, subjective norms, price, and purchase intention. Research design, data, and methodology: The study targets a population of 458 online consumers in China who are 31 years old or over. The validity and reliability of the research are assessed using Item-Objective Congruence (IOC) and Cronbach’s Alpha. To ensure diverse representation, the sampling procedure incorporates a combination of judgmental, stratified random, and convenience sampling methods. The collected data is analyzed through Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) techniques, allowing for a comprehensive examination of the research variables. Results: Perceived usefulness and perceived ease of use influence purchase intention mediated by attitude towards online shopping. Trust and price significantly impact purchase intention. Nevertheless, perceived risk and subjective norms do not significantly impact purchase intention. Conclusion: The conclusions of this study have significant real-world implications for online platforms. Online platforms and merchants may use the results of this study to increase sales and profitability.